Vortex-Antivortex Dynamics in a Mesoscopic Superconducting Prism with a Centered Antidot - Barba-Ortega, J.; Sardella, Edson [UNESP]; Albino Aguiar, J. (Springer, 2011)
In this work, we investigated theoretically the dynamics of the annihilation of a vortex-antivortex pair in a superconducting mesoscopic prism of square transversal section with a square antidot inserted at its center. The sample is immersed in a magnetic field applied perpendicular to the sample plane. It is assumed that the inner hole is made of a material whose properties are accounted on de Gennes boundary conditions via de Gennes extrapolation length (b parameter). We analyze the nucleation of vortices and antivortices by increasing the magnetic field from zero until the first vortex is created and then reversing the polarity of the applied magnetic field until an antivortex is also created. Depending on the b parameter, the vortex-antivortex encounter can take place at the hole or at the superconducting region around it. In the framework of the time dependent Ginzburg-Landau theory, we calculate the magnetization, order parameter topology, the position and the velocity of the vortex and antivortex singularities as a function of time.
Keywords: De Gennes parameter; Ginzburg-Landau; Lorentz force; Pinning force